EXTRACTPRO: A Data Mining Tool for Developer Profile Generation Based on Source Code Analysis - Lopes, Jefferson G. M.; Alves, Johnatan; Figueiredo, Eduardo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
The search for software developers with specific skills is an arduous and expensive task. Nowadays, software developers report their skills on freelance platforms and professional social networks, such as Workana and LinkedIn. However, this information tends to be sparse and difficult to compare. This paper presents EXTRACTPRO, a tool that uses a Developer Information Provider (i.e., Workana) and a Git Repository Provider (i.e., GitHub) to build a searchable collection of developer profiles. This generated developer profile contains self-declared skills in programming languages and mined information, such as lines of code and commit count. In addition to mining profiles, the tool provides a search by the skills with ranked and visually comparable results. We demonstrate the proposed tool by showing examples of use and evidence that the tool can find developers with arbitrary skills. In complement to this paper, a short video demonstration of EXTRACTPRO is also available12.